The Use of Mind-Mapping in Paragraph Writing Learning with Critical Thinking Stimulus for Students - Krisnawati, Vera; Marahayu, Nila Mega; Budi Utami, Shofi Mahmudah; Martha, Nia Ulfa (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This classroom action research aims to (1) improve the quality of the learning process to write paragraphs with a critical thinking stimulus using the mind mapping method and (2) improve the ability to write paragraphs with a critical thinking stimulus using the mind mapping method. The research subjects are students taking Indonesian courses in science and social science majors at Universitas Jenderal Soedirman. Data sources include lesson plans, photos, test results, a list of scores, field notes, and notes on interview results. Data collection techniques were conducted through observation, interviews, tests, and documents. The achievement indicator is 75%. The research procedure includes preparation, initial survey, cycle implementation, observation, and reporting. Mastery of critical thinking skills in writing paragraphs is also reflected through a long continuous process starting from the ability of students to build references and social relationships such as cooperation with other students, communicating with others, tolerance, respecting the opinions of others, and being open to criticism from others. Other aspects observed encompass the ability of students to acquire confidence that is essential to possess the ability and capability to complete learning tasks. Furthermore, students can master the teaching materials that they have studied at least 75% of what should be achieved per the specific instructional objectives intended.